PENILAIAN KINERJA BADAN RUMAH SAKIT UMUM TABANAN BERDASARKAN BALANCED SCORECARD - RASMINI, NI KETUT; SUPADMI, NI LUH; HERAWATI SUCANDRA, NI LUH PUTU (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
As a government’s institution which gives health services, Tabanan General Hospital is one of the regional hospitals which has obtained ISO 9001:2000, meaning that it has fulfilled the standard of the management of quality. Having obtained ISO, its performance is necessarily evaluated both from the financial perspective and the non financial perspective. The problems which are discussed in this research are how good the performance of Tabanan General Hospital was if evaluated from the perspective of Balanced Scorecard such as financial, customers, internal business, and learning and growth perspectives. The performance in the perspective of finance is evaluated with reference to the value for money method, by which the degrees of its economy, efficiency and effectiveness are measured. The performance in the perspective of customer is evaluated with reference to the growth of customer and their satisfaction. The performance in the perspective of the process of internal business is evaluated with reference to the capacity of its infrastructure and the quality of its services. The performance in the perspective of learning and growth is evaluated with reference to the productivity of the staff and their job satisfaction. Based on the analysis carried out, the performance of Tabanan General Hospital from 2004 to 2007 was classified as being economical. However, its performance in 2008 was classified as being not economical. With regard to its efficiency, it was not efficient yet; however, it was classified as being effective. In the perspective of customers, the numbers of customers increased and viewed from their satisfaction, its performance was good enough. Viewed from the perspective of the process of internal business, the increased capacity of the infrastructure and the improved quality of the services, it can be stated that its performance was good enough. In the perspective of learning and growth, which was evaluated with reference to the increased productivity of the staff from 2004 to 2007, its performance fell; however, in 2008 its performance was good which can be seen from the increased productivity of the staff and their improved satisfaction.
Keywords: performance in the perspective of finance, performance in the perspective of customers, performance in the perspective the process of internal business, performance in the perspective of learning and growth